Similarity Index for the Fat Fraction between Breast Milk and Infant Formulas - Hokkanen Sanna; Frey Alexander D; Yang Baoru; Linderborg Kaisa M (AMER CHEMICAL SOC, 2022)
The similarity of the fat fraction in infant formulas rich in either bovine milk fat (MF) or vegetable oil (VO) to breastmilk was evaluated by analyzing their lipid composition. Milk fat-rich formulas were highly similar (average similarity index 0.68) tobreast milk compared to the VO-rich formulas (average similarity index 0.56). The highest difference in the indices was found in thecontents of cholesterol (0.66 vs 0.28 in MF- and VO-rich formulas, respectively, on average) and polar lipids (0.84 vs 0.53), thepositional distribution of fatty acids in thesn-2 position of triacylglycerols (0.53 vs 0.28), and fatty acid composition (0.72 vs 0.54).The VO-based formulas were superior in similarity inn-6 PUFA. Thus, the addition of bovine MF fractions is an effective way toincrease the similarity between the lipid composition of infant formulas and human milk